Interferon-γ Receptor Signaling in Dendritic Cells Restrains Spontaneous Proliferation of CD4+ T Cells in Chronic Lymphopenic Mice - Knop, Laura; Frommer, Charlotte; Stoycheva, Diana; Deiser, Katrin; Kalinke, Ulrich; Blankenstein, Thomas; Kammertoens, Thomas; Dunay, Ildiko Rita; Schüler, Thomas (Frontiers in Immunology, 2019)
In lymphopenic mice, T cells become activated and undergo lymphopenia-induced proliferation (LIP). However, not all T cells are equally sensitive to lymphopenia. Several lymphopenia-insensitive T cell clones were described and their non-responsiveness was mainly attributed to clone-specific properties. Here, we provide evidence for an additional, host-dependent mechanism restraining LIP of lymphopenia-insensitive CD4+ T cells. We show that such cells undergo LIP in lymphopenic mice lacking IFN-γR expression, a process, which is promoted by the autocrine action of T cell-derived IFN-γ. Additionally, LIP of lymphopenia-insensitive CD4+ T cells requires an intact microflora and is accompanied by the massive accumulation of IL-6 and dendritic cells (DCs). Consistent with these results, IL-6 neutralization and the DC-specific restoration of IFN-γR expression are both sufficient to restrict LIP. Hence, the insensitivity of CD4+ T cells to lymphopenia relies on cell-intrinsic properties and a complex interplay between the commensal microflora, IL-6, IFN-γR+ DCs and T cell-derived IFN-γ.